Diglossia and early spelling in Malay - Siew, Amy Chin Ying (Universiti Malaysia Sarawak (UNIMAS), 2014)
Diglossia is a widespread sociolinguistic condition (Schiffman, 1998) where two distinct varieties of the same language (standard and non-standard) coexist in a speech community (Ferguson, 1959). Each of the variety has clear functional separation where the standard language is the superposed variety used in all formal occasions and writings while the non-standard language is the variety used for everyday conversations.